Pemetaan Penelitian Rasio Net Operating Margin (NOM) pada Perbankan Syariah: Studi Bibliometrik VOSviewer dan Literature Review - Budianto, Eka Wahyu Hestya; Dewi, Nindi Dwi Tetria; Selasi, Dini (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2023)
This study aims to determine the research mapping regarding the Net Operating Margin (NOM) ratio in Islamic Banking using a mix-method approach, namely the VOSviewer bibliometric study and literature review. Data analysis techniques include: (1) mapping the distribution of journal publications around the NOM ratio; (2) mapping the results of the VOSviewer bibliometric visualization around the NOM ratio based on the number of clusters and their items; and (3) mapping research topics around the NOM ratio using a literature review study. The results showed that: (1) based on the distribution of journal publications, there were 18 journal publications regarding the NOM ratio; (2) based on the mapping of the VOSviewer bibliometric study, the network visualization results around the NOM ratio are divided into 3 clusters and 58 topic items; (3) based on the mapping of literature review studies, there are 4 topics around the influence of the NOM ratio and 8 topics about the determinants of the NOM ratio. The implications and contributions of this research are to map research topics around NOM ratios in Islamic Banking which are often or rarely researched by researchers so that they can be a reference for subsequent researchers.